2007
DOI: 10.1007/s00775-007-0327-6
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin and siRNA interference with structure and function of Wnt-5a mRNA: design and in vitro evaluation of targeting AU-rich elements in the 3′ UTR

Abstract: Wnt-5a is a secreted glycoprotein which has been shown to be involved in the regulation of cell adhesion and motility, processes which are of importance in metastasis formation by cancer cells. We here present an initial study aiming at evaluating whether small interfering RNA (siRNA) in combination with cisplatin can be used to modulate protein expression levels under in vitro conditions. For this purpose, an AU-rich region corresponding to the initial 260 bases of the Wnt-5a 3' untranslated region was chosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Factors that may be relevant to structurally diverse RNAs have been encountered in studies of platinated DNA hairpins, platinum cross-linked quadruplex structures, and platinated DNA–protein complexes 47–53. Additionally, preliminary investigations have already begun to address cisplatin’s use as a structural probe and as drug conjugate for targeting RNA 15,17,54,55…”
Section: Discussionmentioning
confidence: 99%
“…Factors that may be relevant to structurally diverse RNAs have been encountered in studies of platinated DNA hairpins, platinum cross-linked quadruplex structures, and platinated DNA–protein complexes 47–53. Additionally, preliminary investigations have already begun to address cisplatin’s use as a structural probe and as drug conjugate for targeting RNA 15,17,54,55…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent mechanistic studies have shown that isomerization reactions between these 1,3 G*pNpG* transplatin adducts and complementary oligonucleotides are sequence-specific [91], can result in unusual G-N7* to C-N3* crosslinks [89], and are also observed using 2'-OMe [92] and chemically modified RNAs [93]. Further work has shown that transplatin-modified 2'-OMe RNAs [94] and cisplatinmodified RNAs [95,96] can be used as antisense oligos for attenuating gene expression in cell lysates and in living cells.…”
Section: Transplatin Cross-linking and Pt(ii) Drug Conjugatesmentioning
confidence: 99%
“…26 In the initial study, we were able to observe that, first, both cisplatin and siRNAs were independently able to silence translation. 23 Second, the measured silencing ability after initial transfection of siRNA followed by subsequent cisplatin exposure was found to be additive. It was therefore concluded that cisplatin had a non-significant effect on direct siRNA-induced gene silencing under the experimental conditions used, with short-term evaluation on translational levels (48 h).…”
mentioning
confidence: 98%